Choledochal cysts in pregnancy: Case management and literature review - Wu, De-Quan (World J Gastroenterol, 2004)
AIM: To evaluate the diagnosis, management principles and long-term results of congenital choledochal cysts in pregnancy. METHODS: Three adult patients were diagnosed as choledochal cysts in pregnancy from 1986 to 1989 and their long-term results were evaluated. RESULTS: The first patient had a Roux-en-Y cysto-jejunostomy with T-tube external drainage and died of septic shock and multi-organ failure 25 d after operation. In the second patient, 4 wk after percutaneous trans-choledochal cyst was drained externally with a catheter under US guidance, four weeks later the patient delivered vaginally, and had a cysto-jejunostomy 3 mo after delivery, and lived well without any complications for 15 years after operation. The third patient received Roux-en-Y cysto-jejunostomy after a vertex delivery by induced labor at 28 wk gestation, and demonstrated repetitively intermittent retrograde cholangitis within 10 years, and then died of well-differentiated congenital cholangioadenocarcinoma one month after re-operation with exploratory biopsy at the age of 36. CONCLUSION: More conservative approaches such as external drainage of choledochal cyst should be considered for pregnant patients with high risk, complete excision of choledochal cyst during hepaticojejunostomy or modified hepaticojejunostomy is highly recommended at the optimal time.